Epizootiologic survey of selenium and vitamin E concentrations in dairy cows of Thessaioniki’s county - CHRISTODOULOPOULOS (Γ. ΧΡΙΣΤΟΔΟΥΛΟΠΟΥΛΟΣ), G.; ROUBLES (Ν. ΡΟΥΜΠΙΕΣ), N.; KARATZIAS (Χ. ΚΑΡΑΤΖΙΑΣ), H.; PAPASTERIADIS (Α. ΠΑΠΑΣΤΕΡΙΑΔΗΣ), A. (Journal of the Hellenic Veterinary Medical Society, 2018)
The purpose of this research was the study of selenium (Se) and vitamin E (vit. E) concentrations in dairy cows blood within the region of Thessaloniki. The survey included 65 dairy cow farms in the region of Thessaloniki from which samples of blood were collected from 10 female adult animals from every farm. Out of the total 650 cows examined in the 65 farms, 40% presented deficient concentration of Se in blood (<0,08 μg/ml), 29% marginally deficient concentration (0,08-0,12 μg/ml) and only 31% normal concentration (>0,12 μg/ml). Regarding vit. E, only 4%, out of the 650 cows examined, had deficient concentration in the blood plasma (<2 μg/ml). It was concluded from the above that, in the region of Thessaloniki, a significant percentage of the dairy cows run the risk of Se deficiency diseases. On the contrary, the case of vit. E deficiency, should be regarded as improbable for these animals.